Developing a legal framework for promoting child protection in Malaysia by means of intercountry adoption - A. Kadir, Nadhilah; Che Soh @ Yusoff, Roslina; Mohd, Azizah; Mohd Zin, Najibah; Hamid, Abdul Ghafur@Khin Maung Sein (2015)
Intercountry adoption is recognized at international level as one of the available means for child care. The main international instrument deals with the practice of intercountry adoption is the Hague Convention on Protection of Children and Cooperation in respect of Intercountry Adoption of 1993 (hereinafter referred to as the Hague Convention 1993). Intercountry adoption provides permanent family care for children in need of care and protection especially children without families. Nevertheless, intercountry adoption is not common in Malaysia as a child protection measure. There is no statutory provision regarding intercountry adoption in Malaysia. Malaysia has ratified the United Nations Convention on the Rights of the Child of 1989 (hereinafter referred to as the CRC 1989). However, Malaysia is not a party to the Hague Convention 1993. This paper seeks to examine the applicability of intercountry adoption in Malaysia as an alternative means of child protection for children without families. Examination will be based on interviews with relevant departments and the existing laws on adoption in Malaysia. The paper also examines the international legal framework for intercountry adoption such as the CRC 1989 and the Hague Convention 1993. In addition, this paper will provide a brief comparative review on the practice of intercountry adoption in a Muslim country such as Morocco. The findings of this research will provide relevant suggestion for the practice of intercountry adoption in Malaysia.